2004
DOI: 10.1111/j.0958-7578.2004.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprecipitate prepared from plasma treated with methylene blue plus light: increasing the fibrinogen concentration

Abstract: When cryoprecipitate is prepared from plasma which has been treated with methylene blue plus light (MB) for the purpose of virus inactivation, clottable fibrinogen content is 40% lower compared with units prepared from untreated plasma. Initial studies showed that when frozen MB plasma units were removed to +2 to +6 degrees C for 4 h and then returned to -40 degrees C prior to cryoprecipitation, fibrinogen recoveries increased from 24 to 42%. Although fibrinogen yield improved when plasma units were stored at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Cardigan and colleagues 1 conclude that their study demonstrating satisfactory Factor (F)VIII content in plasma subjected to temperature deviations during −40°C storage “meets EU guidelines and is suitable for transfusion.” In work designed to specify plasma storage conditions for optimal FVIII yield during fractionation, we observed that conditions similar to the temperature fluctuations reported by Cardigan and colleagues resulted in substantial increases in fibrinogen deposition in the cryoprecipitate fraction 2 . This effect was exploited by us 3,4 and others 5,6 to increase fibrinogen content in blood bank cryoprecipitate for transfusion, as well as to moderate fibrinogen content in cryoprecipitate intermediate in FVIII concentrate production, where increased fibrinogen can affect subsequent purification and viral inactivation steps. As a result of this work, we also noted that the total recoverable FVIII after plasma temperature fluctuations was decreased in the cryosupernatant fraction, which has been shown to be associated with low‐molecular‐weight forms of von Willebrand factor and to be more labile than other forms of FVIII 7 .…”
supporting
confidence: 60%
“…Cardigan and colleagues 1 conclude that their study demonstrating satisfactory Factor (F)VIII content in plasma subjected to temperature deviations during −40°C storage “meets EU guidelines and is suitable for transfusion.” In work designed to specify plasma storage conditions for optimal FVIII yield during fractionation, we observed that conditions similar to the temperature fluctuations reported by Cardigan and colleagues resulted in substantial increases in fibrinogen deposition in the cryoprecipitate fraction 2 . This effect was exploited by us 3,4 and others 5,6 to increase fibrinogen content in blood bank cryoprecipitate for transfusion, as well as to moderate fibrinogen content in cryoprecipitate intermediate in FVIII concentrate production, where increased fibrinogen can affect subsequent purification and viral inactivation steps. As a result of this work, we also noted that the total recoverable FVIII after plasma temperature fluctuations was decreased in the cryosupernatant fraction, which has been shown to be associated with low‐molecular‐weight forms of von Willebrand factor and to be more labile than other forms of FVIII 7 .…”
supporting
confidence: 60%
“…factor VIII ≥70% of the value of the freshly collected plasma unit [71]. Experiments have shown that storing MB FFP units at 2-6 °C for 4 or 8 h significantly increases fibrinogen recovery with a concomitant small loss of factor VIII recovery in the cryoprecipitate units [4,72,73].…”
Section: Adherance To Guidelines and Clinical Aspectsmentioning
confidence: 99%
“…These methods are usually used during the manufacturing of a lot of biological products (e.g., biotechnology products, plasma-derived products). Precipitation methods often firstly involve cryoprecipitation and ethanol fractionation (e.g., plasma derived biologicals; Hornsey et al 2004). Other precipitation agents that can be used are polyethylene glycol, methanol, ammonium sulfate, and cationic detergents (Kreis et al 1990;Uemura et al 1994;Burnouf et al 2004).…”
Section: Methods Characteristicsmentioning
confidence: 99%